2022
DOI: 10.1038/s41598-022-06199-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of COVID-19 pneumonia can be early predicted combining Age-adjusted Charlson Comorbidity Index, CRB score and baseline oxygen saturation

Abstract: In potentially severe diseases in general and COVID-19 in particular, it is vital to early identify those patients who are going to progress to severe disease. A recent living systematic review dedicated to predictive models in COVID-19, critically appraises 145 models, 8 of them focused on prediction of severe disease and 23 on mortality. Unfortunately, in all 145 models, they found a risk of bias significant enough to finally "not recommend any for clinical use". Authors suggest concentrating on avoiding bia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Pereira et al, in their COVID-19 SOTRs study, observed a relationship between initially lower oxygen saturation and the risk of hospital admission [ 24 ]. Corresponding results were noted in the general population [ 25 , 26 ]. Thus, baseline health condition and oxygenation status have a crucial impact on therapy outcomes and appear to be of paramount importance in predicting the risk of death or hospital admission.…”
Section: Discussionsupporting
confidence: 80%
“…Pereira et al, in their COVID-19 SOTRs study, observed a relationship between initially lower oxygen saturation and the risk of hospital admission [ 24 ]. Corresponding results were noted in the general population [ 25 , 26 ]. Thus, baseline health condition and oxygenation status have a crucial impact on therapy outcomes and appear to be of paramount importance in predicting the risk of death or hospital admission.…”
Section: Discussionsupporting
confidence: 80%
“…The aCCI is a significant predictor of survival after cancer ( 19 ), infective endocarditis ( 20 ), transcatheter mitral valve repair ( 21 ), and COVID-19 pneumonia ( 22 ). Presently, there are numerous studies on the association between CCI and mortality in patients with hip fracture, all having reported that high CCI scores were associated with mortality or considered high CCI score to be a risk factor ( 8 , 12 , 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous Authors have observed similar findings in their studies. [47][48][49] Surprisingly, 28.18% of cases in Evolved pneumonia phenotype doesn't require either oxygen or oxygen plus ventilatory support. Rational for this observation would be more consolidations and without or with minimal GGOs or crazy paving and more cases in this category were having less than four-fold inflammatory markers.…”
Section: Evolved and Evolving Patterns In Study Cases And Its Correla...mentioning
confidence: 99%